Potensi Ekowisata di Desa Air Hitam Laut Sebagai Desa Penyangga Taman Nasional Berbak Sembilang - Nursanti, Nursanti; Wulan, Cory; Junita, Rika (Fakultas Kehutanan Universitas Jambi, 2018)
This research was conducted with the aim to know the potential of ecotourism that existed in the Air Hitam Laut village and the characteristics of human resources of the people of Air Hitam Laut Village. The study was conducted using the snowball sampling method and the exploratory survey. The result of this research show that ecotourism potential in Air Hitam Laut are: Babussalam beach with Pescaprae formation and Barringtonia formation composed by various types of vegetation; the safari night. The culture and community tradition that can be potential of ecotourism are: Safar shower ritual, village anniversary events, â€œcerak parekâ€, and community activities to find fish in the sea. The potential of ecotourism in the form of historical relics of sacred sites in the form of mini museum hut, as well as the potential of culinary tourism derived from the typical food of the Air Hitam Laut Village community. Characteristics of human resources in the village of Air Hitam Laut, namely the Air Hitam Laut community has a distinctive social life order In terms of economic life of the livelihood of the community is almost the same as fishermen, and farmers, and has a low level of education. In terms of cultural life is still the spirit of mutual help.